Aplikasi Bakteri Fotosintesis dengan beberapa Komposisi Pupuk Kimia terhadap Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.) - Rifatul Qomariah, Indah; Mawardi, Mawardi (JURNAL AGROPLANT, 2024)
Cucumber is a farming commodity which is relatively easy to maintain, inexpensive and short-lived. The prospect of cultivating cucumber plants is very good because cucumbers are much loved by the community. The nutritional value of cucumber is quite good because this fruit vegetable is a source of minerals and vitamins. As cucumber production increases, the development of cucumber plants also often experiences obstacles, especially in terms of soil physical and chemical properties. Continuous application of chemical fertilizers with increasing doses every year can cause the soil to become hard and disrupt the balance of soil nutrients. This research was carried out to reduce the excessive use of chemical fertilizers and as an effort to save money. One of the efforts is by using PSB. This research was carried out in Suka Makmur Hamlet, Ajung District, Jember Regency, East Java from 6 December to 27 January 2022. This study used a Randomized Block Design (RBD) method with 6 treatments and 4 replications. The treatments used were: Control (P0); 5 ml/L PSB (P1); 5 ml/L of PSB and 2g of NPKCaMg (16:16:16:6:0.5) (P2); 5 ml/L of PSB and 2g of NPKCaMg (20:4:4:18:1:1) (P3); 5 ml/L of PSB and 2g of NPKSCaMg (17:12:12:6:4:2) (P4); 5 ml/L of PSB and 2g of NPKSCaMg (20:30:23:2:3:2) (P5). The results showed that the use of photosynthetic bacteria was not able to meet the nutrient requirements for the growth and productivity of cucumber plants. Application of photosynthetic bacteria (5 ml/L) and chemical fertilizers (2g NPKSCaMg (20:4:4:18:1:1)) with a high N content had significantly different effects on fruit number and fruit weight per plant.